The Jobs Crisis : Household and Government Responses to the Great Recession in Eastern Europe and Central Asia - World Bank (World Bank, 2012)
The financial crisis swiftly expanded into an economic crisis throughout America and Western Europe, from where it spread to developing countries that had depended on foreign direct investment, consumer and mortgage credit, trade, and remittances. By early 2009, it was clear that this economic downturn would be more severe than any crisis since the great depression, prompting some to it as the 'great recession.' Eastern European and Central Asian countries were hit particularly hard during 2009, global Gross Domestic Product (GDP) contracted for the first time since Second World War. The financial crisis and the ensuing economic downturn, the worst since the Great Depression in the 1930s, went hand in hand with tightening of credit markets, bank failures, firm closures, and high demand for social safety nets. This report, The jobs crisis: household and Government responses to the great recession in Eastern Europe and Central Asia, brings together evidence that World Bank teams have collected on the impact of the crisis on households and families in Eastern Europe and Central Asia. This report shows how the crisis was felt by Eastern European and Central Asian households. Not only did unemployment rise sharply but it also lasted longer. The report also shows that the pain of the recession was broader, with workers taking home smaller paychecks as firms offered lower wage rates and fewer hours of work to their workers. The jobs crisis finds that households used a variety of ways to cope with the crisis. The jobs crisis presents an account of how governments reacted to the crisis through social policy reforms and initiatives and how such responses could be improved in the future. Unemployment insurance benefits played a particularly important cushioning role, but coverage of the unemployed tended to be limited.